Overcoming dormancy in seeds of Bixa orellana L. - Ítallo Jesus Silva; Deilson de Almeida Alves; Silvia Gabriela Rosa; Vitória Aparecida Porto Lima; Rogério Alves Santana; Marcela Carlota Nery (Scientific Electronic Archives, 2023)
Annatto seeds, Bixa orellana L., have dormancy mechanisms that make their germination difficult, requiring testing of different methods to enable their reproduction. Thus, the objective was to evaluate the emergence of Bixa orellana seeds submitted to solutions and periods of imbibition to overcome dormancy. The experimental design was completely randomized, with a 4×2 factorial arrangement. The evaluated seeds were from the red Piave cultivar, with a solution of distilled water and gibberellic acid (GA3) at a concentration of 125 mg L-1 in the imbibition periods of 0, 4, 10, and 24 hours. Emergence test, shoot height, stem diameter, root length, shoot, and root dry matter, and Dickson's quality index was evaluated. The solutions did not interfere with the development of the plants in the periods. It was concluded that annatto seeds in a GA3 solution for a period of 24 hours are efficient for overcoming dormancy.